2019
DOI: 10.1017/s0305741019001371
|View full text |Cite
|
Sign up to set email alerts
|

Different Demands, Varying Responses: Local Government Responses to Workers’ Collective Actions in South China

Abstract: While Chinese local governments remain extremely wary of workers’ collective actions, they do not always suppress them; sometimes, they tolerate such actions and even seek to placate workers. What accounts for these different government responses to workers’ collective actions? Based on a sample of over 1,491 collective action cases that took place in Guangdong between 2011 and 2016, we find that the types of demands raised by workers during collective actions affect how local governments respond. Local govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…On the contrary, when they abandoned their institutional demand, the state is willing to use the strategy of substitute concessions to pacify workers making sure they received some economic compensation (see Figure 2). My argument is in line with the observation that the state reacted differently to different types of demands made by workers in collective actions (Yang and Chen 2019).…”
Section: Major Argumentssupporting
confidence: 82%
See 1 more Smart Citation
“…On the contrary, when they abandoned their institutional demand, the state is willing to use the strategy of substitute concessions to pacify workers making sure they received some economic compensation (see Figure 2). My argument is in line with the observation that the state reacted differently to different types of demands made by workers in collective actions (Yang and Chen 2019).…”
Section: Major Argumentssupporting
confidence: 82%
“…2 That said, 'the associational power of the workers is[was] still weak' (Leung, 2015: Chapter 7). According to various studies, the Guangdong and central governments have not totally repressed workers making immediate economic demands (Yang and Chen 2019). Indeed, the state has responded less harshly to worker protests since 2000 (Chen 2006).…”
Section: Major Argumentsmentioning
confidence: 99%
“…Chen (2019) has also noted that it is usually difficult to boost solidarity among Chinese workers because civic society organizations are not sufficiently strong to support labor activism. Yang and Chen (2020) have suggested that labor strikes driven by narrow economic demands are not politically daunting. These works imply that some labor strikes are not likely to pose threats to the state.…”
Section: Data Collection and Identification Strategymentioning
confidence: 99%
“…Scholars have maintained that prior to 2010, workers utilised their associational power to pursue immediate economic interests but have since also deployed associational power to form enterprise unions to provide them with workplace institutional power (Hui, 2021a). Third, also focusing on workers’ demands, scholars have differentiated between defensive and offensive actions (Elfstrom and Kuruvilla, 2014; Yang and Chen, 2020). Defensive protests urge employers to fulfil workers’ legal rights, whereas offensive protests strive for treatment beyond minimum legal standards.…”
Section: Labour Activism In Chinamentioning
confidence: 99%
“…The sociological frameworks of defensive versus offensive action and reactive versus proactive action have informed scholars’ conceptualisations of labour protests in the United States (Martin and Dixon, 2010; Naples, 1987), Canada (Brym et al, 2013), France (Perrot, 1974), Italy (Snyder and Kelly, 1976) and Vietnam (Clarke et al, 2007). Influenced by this tradition, some scholars studying labour activism in China have distinguished between defensive and offensive strikes (Elfstrom and Kuruvilla, 2014; Yang and Chen, 2020) and similarly between rights-based and interest-based protests (Chan, 2011). Scholars have contended that labour resistance in China has transformed from defensive to offensive (Elfstrom and Kuruvilla, 2014) or from rights-based to interest-based (Chan, 2011).…”
Section: From Production To Reproductionmentioning
confidence: 99%